Penilaian Implementasi Rekam Medis Elektronik Dengan Metode HOT-FIT di Puskesmas Kota Padang - Siswati, Sri; Syafrawati; Khairunnisa, Muthia (LPPM Hang Tuah Pekanbaru, 2025)
The implementation of Electronic Medical Records (EMR) in public health centers by December 31, 2023, as mandated by the Ministry of Health Regulation No. 24 of 2022, faces challenges in human, organizational, and technological aspects. This study evaluates the EMR system in public health centers in Padang using the HOT-FIT method through a mixed-method approach conducted from April to June 2024. Quantitative data were collected through a cross-sectional survey of 72 respondents (doctors, medical record staff, nurses) and qualitative data from 48 informants (heads of health centers, medical record staff). The findings indicate that in the human aspect, system usage was rated good (54.2%), but user satisfaction was low (58.3%). Organizational aspects, including structure (52.8%) and environment (54.2%), were rated good. In the technology aspect, system quality (51.4%) and information quality (56.9%) were rated poor, while service quality was rated good (62.5%). The net benefit aspect (55.6%) highlighted EMR's contribution to improving work efficiency and effectiveness. Challenges include insufficient training, low technological literacy, network disruptions, inadequate infrastructure, weak patient data security, and incomplete patient records. The study recommends the development of a mayoral regulation to address these challenges and enhance EMR implementation in Padang.